2021
DOI: 10.1002/advs.202100250
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase (FAK) Inhibition Synergizes with KRAS G12C Inhibitors in Treating Cancer through the Regulation of the FAK–YAP Signaling

Abstract: KRAS mutation is one of the most prevalent genetic drivers of cancer development, yet KRAS mutations are until very recently considered undruggable. There are ongoing trials of drugs that target the KRAS G12C mutation, yet acquired drug resistance from the extended use has already become a major concern. Here, it is demonstrated that KRAS G12C inhibition induces sustained activation of focal adhesive kinase (FAK) and show that a combination therapy comprising KRAS G12C inhibition and a FAK inhibitor (IN10018) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 64 publications
0
25
1
Order By: Relevance
“…In addition, the resistant tumor was found to have a significantly reduced adaptive immune cell population. 53 Zhang et al 54 found that focal adhesion kinase activity is induced when KRAS G12C is inhibited and may result in tumor fibrosis as a potential mechanism of acquired drug resistance. Cell lines and patient-derived xenograft models from lung and colon adenocarcinoma samples were identified by Hallin et al 55 as having not only resistance mechanisms in RTKs but also genetic dysregulation of the cell cycle.…”
Section: Pathway Activation Via Rtks Upstream Of Kras and Ras/ Mapk A...mentioning
confidence: 99%
“…In addition, the resistant tumor was found to have a significantly reduced adaptive immune cell population. 53 Zhang et al 54 found that focal adhesion kinase activity is induced when KRAS G12C is inhibited and may result in tumor fibrosis as a potential mechanism of acquired drug resistance. Cell lines and patient-derived xenograft models from lung and colon adenocarcinoma samples were identified by Hallin et al 55 as having not only resistance mechanisms in RTKs but also genetic dysregulation of the cell cycle.…”
Section: Pathway Activation Via Rtks Upstream Of Kras and Ras/ Mapk A...mentioning
confidence: 99%
“…This combination simultaneously reduces the degree of drug resistance. The synergistic benefit of the combination therapy was consistently observed in different CDX and PDX models of KRAS (G12C) cancers [ 122 ]. Besides, activation of the FAK signaling pathway has an impact on the tumor microenvironment [ 123 , 124 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings open new opportunities to explore other receptors such as FAK (focal adhesion kinases) that have already been related in KRAS mutant patients. FAK may be surrogate markers of aberrant KRAS signaling found in aggressive phenotype in lung cancer [ 29 ]. A similar effect was observed in the KRAS -mutated adenocarcinoma cell line model (A549-FL), used to examine the metastasis mechanisms that identified epithelial–mesenchymal transition (EMT) markers [ 30 ].…”
Section: Discussionmentioning
confidence: 99%